2013
DOI: 10.1017/jrr.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Couple Satisfaction: The Mediating Effect of Approach and Avoidance Commitment

Abstract: Satisfactory couple relationships are demonstrated to have a myriad of benefits. However, the ability to establish couple satisfaction is shown to be strongly and negatively impacted by insecure romantic attachment patterns (i.e., anxious and avoidant attachment). This study sought to gain an enhanced understanding of the aforementioned link by means of investigating a novel mediator model incorporating two facets of romantic commitment: approach commitment (the desire to maintain a relationship due to benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…Recent empirical evidence points to the great impact that romantic attachment can have on overall family functioning as well as on romantic relationship processes (Hadden, Rodriguez, Knee, DiBello, & Baker, ; Pedro, Ribeiro, & Shelton, ). Additionally, a number of the most influential studies, some of which include actor–partner models, have shown strong empirical support linking one's own attachment (i.e., romantic and general) security with greater relationship satisfaction and one's own attachment insecurity with lower relationship satisfaction (Brassard et al, ; Brennan et al, ; Dandurand, Bouaziz, & Lafontaine, ; Feeney, Noller, & Callan, ; Molero, Shaver, Fernández, Alonso‐Arbiol, & Recio, ; Simpson, , ; Simpson & Rholes, ). Given the large body of research on the subject, Mikulincer and Shaver () provided an exhaustive review of the existing literature.…”
Section: Attachment Trust and Relationship Satisfactionmentioning
confidence: 99%
“…Recent empirical evidence points to the great impact that romantic attachment can have on overall family functioning as well as on romantic relationship processes (Hadden, Rodriguez, Knee, DiBello, & Baker, ; Pedro, Ribeiro, & Shelton, ). Additionally, a number of the most influential studies, some of which include actor–partner models, have shown strong empirical support linking one's own attachment (i.e., romantic and general) security with greater relationship satisfaction and one's own attachment insecurity with lower relationship satisfaction (Brassard et al, ; Brennan et al, ; Dandurand, Bouaziz, & Lafontaine, ; Feeney, Noller, & Callan, ; Molero, Shaver, Fernández, Alonso‐Arbiol, & Recio, ; Simpson, , ; Simpson & Rholes, ). Given the large body of research on the subject, Mikulincer and Shaver () provided an exhaustive review of the existing literature.…”
Section: Attachment Trust and Relationship Satisfactionmentioning
confidence: 99%
“…al., 1993;Kiecolt-Glaser et al, 1993;Beach, Smith, & Fincham, 1994;Forthofer et. al., 1996;Sinclair, & Nelson, 1998;Dandurand, Bouaziz, & Lafontaine, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study attempting to show the mediating role of commitment between attachment and satisfaction, the results revealed that anxious attachment was related with higher dedication and constraint commitment while avoidant attachment was negatively linked with dedication and no relation with constraint commitment; and dedication but not constraint commitment predicted satisfaction (Dandurand, Bouaziz, & Lafontaine, 2013).…”
Section: Studies On Attachment and Commitmentmentioning
confidence: 91%
See 1 more Smart Citation
“…Attachment is also associated with assessment of commitment benefits. Indeed, anxious attachment is correlated with both more awareness of the benefits of the romantic relationship and the costs for its dissolution, while avoidant attachment is correlated with less awareness of the positive aspects of the relationship (Dandurand, Bouaziz, & Lafontaine, 2003).…”
Section: Parental Divorce and Attitudes Of Offspring Toward Divorce Amentioning
confidence: 99%